PENGHINDARAN PAJAK: KARAKTER EKSEKUTIF, KOMITE AUDIT, KONEKSI POLITIK, DAN KUALITAS AUDIT - Irsyad Ardian Pratama (2022)
This study was conducted to determine the effect of the executive character, audit committee, political connections, and audit quality on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 - 2020. This study is a type of quantitative research that uses secondary data. in the form of financial reports and company annual reports. The sampling method in this study used purposive sampling to produce as many as 79 samples of manufacturing companies. The data analysis technique in this study used a panel data regression model selection test, classical assumption test, hypothesis testing, and multiple linear regression testing. Based on the results of data analysis, it can be concluded that the character of the executive, audit committee, and political connections do not have a significant effect on tax avoidance. Meanwhile, audit quality has a significant effect on tax avoidance. Keywords: Tax Avoidance; Audit Committee; Political Connection; Audit Quality